Effect of Biological Fertilizer and Chemical Fungicide on Fusarium Wilt Disease, Growth and Yield on Onion (Allium ascaloncum L) - Rafit Syarifudin; A.Marthin Kalay; Costanza Uruilal (Agrologia, 2021)
Onion (Allium Ascalonicum L) are one of the leading horticultural commodities that have economic value. In cultivation, Fusarium wilt disease is often damaged caused by the fungus Fusarium oxysporum. This study aimed to examine the effect of biofertilizer application on fusarium wilt disease, growth and yield of onion. The treatments tested were Bion-up biofertilizer, KIBRT, Biostimulant, Azoto-Tricho, anthracol fungicide, and without biological fertilizer as a control. Using a randomized block design with three replications. Observation variables were the incidence of fusarium wilt disease, plant height, number and weight of tubers. The results showed that the application of biofertilizers (Bion up, KIBRT, Biostimulants and Azoto-Tricho) was effective in increasing plant height, number of bulbs, and bulb weight of onion bulbs, while controlling the development of fusarium wilt disease was more effective when using Bion up, KIBRT, and Azoto-Tricho.Keywords: Biofertilizer, Antracol, Shallots, Fusarium oxysporum